Golo rebro road tunnel crossing the Labot/Lavanttal tectonic zone - Budkovič, Tomaž; Čarman, Magda; Petkovšek, Borut (Geologija, 2007)
The motorway tunnel Golo rebro is situated on Styrian motorway. It intersects eastern part of Konjiška gora. From the north to the south it intersects the following rocks: paleozoic clastic rocks (inner part of the Labot/Lavanttal fault zone), slope debris with clay matrix (probabbly of tertiary or quartenary age), dolomite, dolomitized limestone and limestone, carbonate breccia and dolomite, dolomitized limestone and limestone, which are partly converted into tectonic breccia. Carbonate rocks are of middle triassic - anisian age. Rocks are strongly tectonised.